On Status Assessment and Management Strategy Formulation for Sustainable Aquaculture of the Hoven’s Carp (Leptobarbus hoevenii, Bleeker, 1851) in Jambi Municipality - Ena Sutisna; Ridwan Affandi; Mohammad Kamal; Gatot Yulianto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Hoven’s carp is an indigenous species of freshwater fish which is hihgly potential to be cultured in larger scale. It is omnivorous tend to be herbivorous fish so that it can save cost of feed. Sustainable management is needed in order to optimize the benefits that can be obtained from hoven’s carp aquaculture activities. It needs to pay attention to four dimensions of sustainable development (ecological, economic, socio-cultural and technological) to avoid problems of aquaculture. The purpose of this study was to assess the status and management strategy formulation for sustainable aquaculture of hoven’s carp in Jambi municipality using the Rapfish application. The results of the sustainability analysis of hoven’s carp aquaculture in Jambi municipality showed less sustainable with an index value of 46.60%, a stress value of 12.93% and a R2 value of 95.72%. Based on the leverage analysis, there are 14 sensitive attributes that are used to improve the sustainability of hoven’s carp aquaculture including availability of aquaculture land, land carrying capacity, marketing access, efficiency in the marketing chain, price fluctuations, availability of venture capital, knowledge of hoven’s carp fish aquaculture, fish farming experience, level of independence of farmers, availability of broodstock and seed, availability of supporting containers for aquaculture, feed independence.